Sharf on the actors of non-bank foreign exchange business (kupva bb) or money changer - Rima Rahmayanti; Rizky Maidan Ilmy; Mustofa Hasan (Faculty of Economics and Business Mulawarman University, 2019)
The phenomenon of the problem in this study is that there are non-bank foreign exchange (KUPVA) or money changer business people who are not licensed or illegal which are feared to be misused for terrorism, drug transactions and money laundering. Therefore, money changer business people are obliged to make permits to the government for business continuity that is licensed and can be trusted by the public. The purpose of this research is to find out how the provisions of sharf for non-bank foreign exchange business activities. The research method used is descriptive qualitative. The results of the study explained that running a business as a non-bank foreign exchange business activity is permitted as long as it must be comply with the provisions set by the government and the conditions stipulated by the MUI fatwa council, including taking care of permits, not for speculation (chancy), there transaction needs or just in case (deposits), if the transaction is carried out on a similar currency then the value must be the same and in cash (at-taqabudh) if different types must be made with the exchange rate that applies when the transaction is carried out and cash.